Eficiência bioeconômica, exigências de energia líquida de mantença e produção de metano de ovinos localmente adaptados à região semiárida - Costa, Clésio dos Santos (2021)
It was the objective of this study to evaluate the productive efficiency of Santa Inês females fed with two nutritional plans of maturity, early and late, with and without adjustment of 15% in the recommendations of protein and total digestible nutrients. The experiment was carried out at the Semiarid Respirometry Lab of Caprine and Ovine Embrapa, in Sobral, Ceará. FIRST CHAPTER - In this study the objective was to evaluate the consumption, digestibility, nitrogen balance, microbial synthesis and the profile of blood metabolites in the growth phase. The 15% nutrient restriction influenced (P<0.05) the reduction of digestibility of late maturity diets. The early maturity plan presents (P<0.05) lower protein digestibility. The unrestricted early maturity diet provides lower fiber digestibility. There was an effect (P<0.05) on dry matter intake, and the lowest value recorded was observed for diets of early maturity without restriction. The adoption of 15% nutrient restriction for the late maturity plan resulted in lower crude protein consumption. There was an effect (P<0.05) on fiber consumption; the lowest consumption was observed for diets of early maturity and, with the use of restriction, an increase was observed. The consumption of total digestible nutrients was lower with the adoption of the late maturity plan with restriction. Late maturity diets have higher nitrogen losses when compared to early maturity diets. The use of restriction also contributed (P<0.0) to the increase in losses trough feces and urine. The late maturity diet showed greater microbial synthesis as the use of restriction only reduced the consumption of metabolizable protein in animals that received this diet. The diets did not affect (P>0.05) the levels of total protein, albumin (g dL-1) and bilirubin (mg dL-1) in the blood. Effect (P<0.05) of diets on blood urea levels (mg dL-1) was observed, with the lowest values observed in diets of early maturity. Restriction influenced urea levels only for late maturity diets. The late maturity diet provided lower values of creatinine, glucose, triglycerides and cholesterol. The use of the 15% restriction is recommended for early maturity diets. For the late maturity plan, the use of dietary restriction is not recommended. SECOND CHAPTER - In this chapter, the objective was similar to the first chapter’s, but it was developed in females above eight months old. The 15% nutrient restriction influenced (P<0.05) the reduction of digestibility of late maturity diets. The early maturity plan presents (P<0.05) lower protein digestibility. The unrestricted early maturity diet provides lower fiber digestibility. There was an effect (P<0.05) on dry matter intake and the lowest value recorded was observed for diets of early maturity without restriction. The adoption of 15% nutrient restriction for the late maturity plan resulted in lower crude protein consumption. There was an effect (P<0.05) on fiber consumption; the lowest consumption was observed for diets of early maturity and, with the use of restriction, an increase was observed. The consumption of total digestible nutrients was lower with the adoption of the late maturity plan with restriction. Late maturity diets have higher nitrogen losses when compared to early maturity diets. The use of restriction also contributed (P<0.0) to the increase in losses trough feces and urine. The late maturity diet showed greater microbial synthesis as the use of restriction only reduced the consumption of metabolizable protein in animals that received this diet. The diets did not affect (P>0.05) the levels of total protein, albumin (g dL-1) and bilirubin (mg dL-1) in the blood. Effect (P<0.05) of diets on blood urea levels (mg dL-1) was observed. The lowest values were observed with diets of early maturity. Restriction influenced urea levels only for late maturity diets. The late maturity diet provided lower values of creatinine, glucose, triglycerides and cholesterol. The use of the 15% restriction is recommended for early maturity diets. For the late maturity plan, the use of dietary restriction is not recommended. THIRD CHAPTER - The objective of this chapter was to evaluate the energy partition, methane production and net energy requirements for the maintenance of Santa Inês females in the growth phase. Diets did not influence (P>0.05) gross energy intake (Kcal day-1; Kcal kg0,75 day-1). An effect (P<0.05) was observed for digestible energy intake, in which the lowest intake was checked in diets of late maturity with restriction. Dietary restriction reduced (P<0.05) the consumption of metabolizable energy. Diets did not influence energy balance (Kcal day-1; Kcal kg0,75 day-1). The early maturity diet provides higher metabolizability value and digestible energy/metabolizable energy ratio. Heat production reduced (P<0.05) with dietary restriction. The unrestricted early maturity diet provides lower methane production. It was observed that the nutritional plans of early and late maturity influenced the estimate of net energy requirements for maintenance, values of 86.16 and 69,05 Kcal kg0,75 day-1 were recorded, respectively. The energy use efficiency values were 0.83 and 0.72 for the early and late maturity plans, respectively. The early maturity plan results in lower methane production. The net energy requirements of maintenance were influenced by nutritional plans and the energy requirements of locally adapted animals diverged from the recommendations of international committees. FOURTH CHAPTER - In this chapter, the objective was similar to the third chapter’s, but it was developed in females above eight months old. The diets did not influence (P>0.05) the consumption of gross energy, energy, digestible energy, metabolizable energy and energy balance (Kcal day-1; Kcal kg0,75 day-1). Gross energy digestibility, metabolizability and the metabolizable energy/digestible energy ratio were influenced (P<0.05), with the highest values observed for diets of early maturity. Dietary restriction reduced (P<0.05) the heat production of the animals. The lowest production was recorded for the animals that received the diet of the early maturity plan without restriction and the highest production went to the late maturity plan with restriction. Maturity nutritional plans did not influence estimates of net maintenance energy requirements for maturing females. Values of 71.5 (Kcal kg0,75 day-1) were recorded. The metabolizable energy maintenance requirement was 82.3 (Kcal kg0,75 day-1) and an energy use efficiency of 0.87 was observed for Santa Inês females. The early maturity plan results in lower methane production. The energy requirements of locally adapted animals diverge from the recommendations of international committees. FIFTH CHAPTER - In this chapter, the objective was to evaluate the dietary restriction of crude protein (CP) and total digestible nutrients (TDN) on the growth curve of Santa Inês females in feedlot. Initial live weight (kg), final live weight (kg), average daily weight gain, dry matter intake (day-1, % of live weight and % of metabolic weight), feed efficiency and residual feed intake (day-1) were not influenced (P > 0.05) by the evaluated diets. However, the relationship between average daily gain and dry matter intake (% of live weight and % of metabolic weight) was influenced (P < 0.05) by diets with restriction of 15% CP and TDN in the second evaluation phase. Applying the model identity test, it was observed that the tested restriction models (ω1; ω2; ω3 and ω4) did not differ (P < 0.05) from the complete model for early maturity diets with and without restriction. This allowed the use of only one curve to describe the growth pattern of these animals. On the other hand, there was an effect (P > 0.05) for the restricted model compared to the complete model of animals submitted to late maturity diets with and without restriction. The animals submitted to early maturity diets with and without restriction showed a maximum growth rate at 170 days, whereas those submitted to late maturity diets without restriction showed the peak of growth at 200 days. In summary, the use of 15% restriction of CP and TDN did not affect the growth parameters of Santa Inês females. However, for late maturity diets, diets without restriction of CP and TDN should be used. SIXTH CHAPTER - In this chapter, the objective was to evaluate the bioeconomic efficiency of Santa Inês lambs submitted to nutritional plans. Eight simulations of production systems were carried out taking into account two nutritional plans (late and early maturity diets) and two forms of recommendation (with and without restriction of 15% of dietary nutrients). The animals were submitted to two periods of confinement (70 and 120 days) and the simulations were performed considering the termination of 300 lambs per year. In summary, the use of late maturity diets without restriction is indicated for the termination of Santa Inês lambs in both periods of confinement, whereas the use of restricted diets is not recommended. For the early maturity plan with a confinement period of 105 days, it is recommended to use the diet without nutrient restriction; when opting for the use of 70 days, it is recommended to use the diet with nutrient restriction